ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN TERBUKA DI KABUPATEN/KOTA PROVINSI JAWA BARAT - Nur Khaliza Dewanti (2024)
West Java occupies first position with the highest open unemployment rate among other provinces in Indonesia. High unemployment has the potential to harm the economy and hinder development. There are several factors that influence unemployment in West Java, including the Labor Force Participation Rate, Human Development Index, and Regency/City Minimum Wage. The aim of this research is to find out how TPAK, HDI, and UMK influence district/city TPT in West Java Province. Within ten years 2013-2022 and 27 districts/cities are the data used in this research using FEM model panel data analysis. The research results show that the Labor Force Participation Rate has a negative but not significant effect on the Open Unemployment Rate, the Human Development Index has a significant negative impact on the Open Unemployment Rate, and the Regency/City Minimum Wage has a significant positive effect on the Open Unemployment Rate. The variables TPAK, HDI, TPT together have a significant effect on TPT.